ASSESSMENT OF LEAD AND CADMIUM IN POWDERED EYE SHADOW SOLD IN LOCALLY MARKETED IN BAQUBA, DIYALA, IRAQ - Ekhlas A. Abdul Kareem; Alaa Esa Sultan; Hiba B. Deab (Scholar Express Journals, 2022)
It has been proven that many consumer products such as cosmetics are contaminated with varying levels of heavy metals. So, in this study we evaluated the level of heavy metals like lead(Pb) and cadmium(Cd) in cosmetic products sold in locally marketed in Baquba, Diyala, Iraq. The cosmetic items included Eye Shadow. The eye makeup was analyzed in triplicate using aflame atomic absorption spectrophotometer (FAAS). After they have been analyzed. The results revealed that the level of Lead in the samples ranged from (<0.01 – 8.99) ppm and cadmium ranged from (><0.01 –1.58) ppm. The results were compared with international standards and were found to be within the limits set by the cosmetic standards of WHO, Canada and US FDA. The results from this study has shown that the daily use of these eye shadow exposes users to some level of concentration of these heavy metals which could constitute potential health hazard due to their ability to bio-accumulate. Therefore, that good manufacturing practice of cosmetic products should be applied in order to ensure the absence of harmful levels of impurities in the ingredients. Antibacterial activity shows that the (un-use) intact eye shadow samples had an inhibitory effect on Staphylococcus epidermidis and Escherichia coli bacteria used, while some samples (in- use) had an effect of increasing the activity of Staphylococcus epidermidis bacteria, For the same brands. We conclude from this study that consumers contribute to contamination of their eye make-up, and this is what was shown by the results of biological activity.>
Keywords: Environmental pollution; Eye shadow; Lead; Cadmium